Pola dan Parameter Pertumbuhan Ikan Tangkapan Dominan (Oreochromis niloticus, Osteochilus sp. dan Xiphophorus helleri) di Danau Buyan Bali - I Made Suma Krisna Sravishta; I Wayan Arthana; Made Ayu Pratiwi (Journal of Marine and Aquatic Sciences, 2018)
Bali Province has four lakes one of them is Buyan Lake. The benefits of Buyan Lake are as a reserve of water used to flow agriculture, settlements and for tourism attraction. In addition there is also the potential of Buyan Lake natural resources of fish is quite abundant. But there are threats arising from the utilization in Buyan Lake so it is feared to disrupt the growth of fish. Therefore it is necessary to do research concern with growth pattern and parameter of dominant catch fish in Buyan Lake. The aimed of this research was to determined the composition of fish catches, estimate the frequency distribution of fish catches and estimate growth patterns and growth parameters of dominant catch fish in Buyan Lake. This research was conducted from February to March 2017. There were nine species captured during observation such as Oreochromis niloticus, Osteochilus sp., Xiphophorus helleri, Rasbora lateristriata, Cyprinus carpio L, Amatitlania nigrofasciata, Puntius sp., Clarias gariepinus and Macrobrachium rosenbergii. The growth pattern of Oreochromis niloticus, Osteochilus sp. and Xiphophorus helleri in Lake Buyan have the same growth pattern that were allometric negative (b <3). Oreochromis niloticus growth parameter obtained L? of 255.1926 mm, K value of 0.2833, t0 value of -0.3260, Osteochilus sp. growth parameter obtained L? value of 251.3837 mm, K value of 0.5261 t0 value of -0.1697, Xiphophorus helleri growth parameter obtained L? value of 82.5826 mm, K value of 0.2379, t0 value of -0.5338. Osteochilus sp. had the highest growth coefficient of 0.5261.